2001
DOI: 10.1007/s100670170101
|View full text |Cite
|
Sign up to set email alerts
|

Subsets in Psoriatic Arthritis formed by Cluster Analysis

Abstract: The aim of the study was to create subgroups among psoriatic arthritis patients on the basis of dermatological features, clinical pattern of arthritis, and laboratory, immunological and radiological findings. Data on 100 patients were expressed in a standardised form and entered into hierarchical cluster analysis according to Ward's method. Seven subgroups were created. Fifty-six patients with mild psoriasis were sorted into a 'polyarticular group'. Two 'RA-like groups' were formed, differing from each other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Factor analysis and clustering methods were applied to discover the relationship between clinical variables measured in the study sample. Related statistical methods have frequently been successfully applied in other fields of medicine (9)(10)(11)(12)(13)(14)(15)(16)(17), and very recently in dermatology (18)(19)(20)(21). Using such a methodology, we were able to identify six statistically different groups of patients characterized by specific association of clinical characterictics.…”
Section: Introductionmentioning
confidence: 99%
“…Factor analysis and clustering methods were applied to discover the relationship between clinical variables measured in the study sample. Related statistical methods have frequently been successfully applied in other fields of medicine (9)(10)(11)(12)(13)(14)(15)(16)(17), and very recently in dermatology (18)(19)(20)(21). Using such a methodology, we were able to identify six statistically different groups of patients characterized by specific association of clinical characterictics.…”
Section: Introductionmentioning
confidence: 99%
“…Ankylosing spondylitis (AS), the prototype of the SpA with a predominant spinal involvement, is a male predominant disease,1 while psoriatic arthritis (PsA) is generally considered a disease that affects men and women equally 2–6. However, a few studies suggested that PsA is more prevalent in male subjects79 while others have shown a female predominance 10 11…”
mentioning
confidence: 99%
“…For example, finger arthritis has been classified based on the finger(s) affected, gender, and biomarkers. 26 Analogously, knee OA could be classified based on the size of the cartilage lesions in the compartments of the joint. Once samples are classified into groups, mean lesion topographies can be determined for each group to identify characteristic patterns.…”
mentioning
confidence: 99%